THE DIFFERENCES VALUE OF P-LCR, THE Β-THROMBOGLOBULIN LEVEL, THE FIBRIN DEGRADATION PRODUCTS LEVEL IN PRE AND POST-HEMODIALYSIS - Like R N; Purwanto A P; Dian W (Indonesian Association of Clinical Pathologist and Medical laboratory, 2018)
Hemostasis disorders in End Stage Renal Disease (ESRD) might be due to uremia syndrome which causing platelet dysfunction. This condition was worsened by chronic hemodialysis which affected the biologic compound degranulation of thrombogenic β-thromboglobulin causing morphological changes of platelets which could be evaluated by using the value of Platelet Large Cell Ratio (P-LCR) and triggering fibrinolysis hyperactivation which increased the Fibrin Degradation Products (FDP) level. The sequence of this mechanism happened continuously. The platelet index evaluation could decide the prognosis after hemodialysis, in addition to monitoring creatinine levels. This study aimed to prove the difference between P-LCR, β-thromboglobulin level, FDP level and creatinine level between pre and post-hemodialysis. The design of this study was observational analytical. Forty-five samples were examined by complete blood count examination using flowcytometry method, the level of β-TG examination by ELISA method, the level of FDP examination by the immunoturbidimetric method and the level of creatinine examination by enzymatic method. The statistical analysis used the Wilcoxon test. It was found that the value of P-LCR in ESRD pre-hemodialysis was higher than in post-hemodialysis with the median 26.8 fl and 25.4 fl, the β- thromboglobulin level increased inpost-hemodialysis compared to pre-hemodialysis (median 200.88 pg/mL and 313.48pg/mL), the FDP level was higher in post-hemodialysis compared to pre-hemodialysis, (median 1.15 µg/mL and 1.7µg/mL), the creatinine level was lower in post-hemodialysis compared to pre-hemodialysis, (median 13.04 mg/dL and 4.56 mg/dL). Therefore, the statistical value was p<0.01. There were significant differences in P-LCR-value, β-thromboglobulin level, fibrin degradation products level and creatinine level between pre and post-hemodialysis.